The Kinome of Edible and Medicinal Fungus Wolfiporia cocos - Wei, Wei; Shu, Shaohua; Zhu, Wenjun; Xiong, Ying; Peng, Fang (Frontiers in Microbiology, 2016)
Wolfiporia cocos is an edible and medicinal fungus that grows in association with pine trees, and its dried sclerotium, known as Fuling in China, has been used as a traditional medicine in East Asian countries for centuries. Nearly 10% of the traditional Chinese medicinal preparations contain W. cocos. Currently, the commercial production of Fuling is limited because of the lack of pine-based substrate and paucity of knowledge about the sclerotial development of the fungus. Since protein kinase (PKs) play significant roles in the regulation of growth, development, reproduction and environmental responses in filamentous fungi, the kinome of W. cocos was analyzed by identifying the PKs genes, studying transcript profiles and assigning PKs to orthologous groups. Of the 10 putative PKs, 11 encode atypical PKs, and 13, 10, 2, 22, and 11 could encoded PKs from the AGC, CAMK, CK, CMGC, STE and TLK Groups, respectively. The level of transcripts from PK genes associated with sclerotia formation in the mycelium and sclerotium stages were analyzed by qRT-PCR. Based on the functions of the orthologues in Sclerotinia sclerotiorum (a sclerotia-formation fungus) and Saccharomyces cerevisiae, the potential roles of these W. cocos PKs were assigned. To the best of our knowledge, our study is the first identification and functional discussion of the kinome in the edible and medicinal fungus W. cocos. Our study systematically suggests potential roles of W. cocos PKs and provide comprehensive and novel insights into W. cocos sclerotial development and other economically important traits. Additionally, based on our result, genetic engineering can be employed for over expression or interference of some significant PKs genes to promote sclerotial growth and the accumulation of active compounds.